Analysis on the hotspot characteristics of bird diversity distribution along the continental coastline of China - Hou, Peng; Bai, Junjun; Chen, Yan; Hou, Jing; Zhao, Jiajun; Ma, Yutiao; Zhai, Jun (Frontiers in Marine Science, 2022)
The continental coastline of China distributes some coastal wetlands with rich biodiversity. To clarify the spatial distribution of bird biodiversity in coastal areas, based on the MaxEnt model and GIS spatial analysis, the distribution data of 488 species of birds and 15 environmental variables were used to simulate the suitable distribution areas of birds, and to analyze the spatial distribution and hotspots of bird biodiversity in coastal areas. The main findings of this study are as follows. (1) 488 species of birds were involved in the modeling of coastal areas, and main environmental factors affecting the potential distribution of birds in general are: land use, monthly mean diurnal temperature range, and precipitation of the driest month. (2) The bird richness high value areas are described according to the four sea areas: In the Bohai Rim, they are mainly distributed in the Liaohe Estuary Wetland, the vicinity of the Yongding River and Haihe River, and the Yellow River Delta Wetland; In the coastal area of the Yellow Sea, they are primarily found in Kunyu Mountain National Nature Reserve, Laoshan Provincial Nature Reserve, and Yancheng Wetland Rare Birds National Nature Reserve; In the coastal areas of the East China Sea, they are mainly found at the mouth of the Yangtze River, at the national nature reserve of Dongtan birds on Chongming Island, near the Min River and along the coast of Quanzhou; In the coastal areas of the South China Sea, they are mainly distributed in the Pearl River Delta wetlands, the southeastern coastal areas of the Guangdong-Hong Kong-Macao Greater Bay Area, and the Shiwanda Mountain National Nature Reserve. (3) The spatial trends in the distribution of hotspots of birds of national priority protection in coastal areas are generally consistent, but more concentrated than the distribution of all birds. (4) After the high-value areas of bird richness were superimposed with protected areas, it was found that the intersecting area accounted for a small proportion of the protected area, and many areas near the inland had low bird richness. Finally, the findings provide references for bird biodiversity conservation and planning in coastal areas.